2012
DOI: 10.1380/ejssnt.2012.374
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Carbonaceous Material Produced from Fireproofed Cotton and Its Adsorption of Methylene Blue

Abstract: We report herein on the fabrication of carbonaceous material produced from cotton treated with Tricresyl phosphate (TCP) for fireproofing and its evaluation for adsorbing Methylene blue (MB). We prepared two carbonaceous materials: cotton calcined at 900• C (CT900) and cotton calcined at 900• C with TCP (F-CT900). These materials were evaluated in terms of their scanning electron microscope images, specific surface area, pore volume, mean pore diameter, and solution pH. We found that the specific surface area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…However, singular adsorbent treatment did not exhibit satisfactory removal of removal of dye and COD in wastewater containing dye. Previous studies reported that the dye adsorption capacity depended on the specific surface area (a physical property) [18][19][20]. Similar trends were observed in this experiment.…”
Section: Removal Of Dye and Cod By Adsorbent Treatmentsupporting
confidence: 90%
“…However, singular adsorbent treatment did not exhibit satisfactory removal of removal of dye and COD in wastewater containing dye. Previous studies reported that the dye adsorption capacity depended on the specific surface area (a physical property) [18][19][20]. Similar trends were observed in this experiment.…”
Section: Removal Of Dye and Cod By Adsorbent Treatmentsupporting
confidence: 90%